PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN ROYAL DENAI HOTEL BUKITTINGGI - SE, MM, YULHASLINDA (Menara Ilmu, 2018)
Denai Hotel Bukittinggi. The purpose of this study was to find the influence of organizationalcommitment to employee performance Royal Denai Hotel Bukittinggi. The population in thisstudy were all employees of Royal Denai Hotel Bukittinggi as many as 58 people. Sampling inthis study conducted by census. The analytical tool used by using structural equation modelPartial Least Square (PLS) .From the results of the analysis found that the relationshipbetween organizational commitment has a positive relationship with the performance of 0626,organizational commitment is a variable that needs to be improved to achieve the performanceof employees in order to provide services prima on a Royal Denai Hotel Bukittinggi. Based onthe results of this study in an effort to improve employee performance. Leaders and employeesof Royal Denai Hotel Bukittinggi can do and enhance the organizational commitment(affective, normative, continue1) which aims to reduce turover with employees so as to createa good working atmosphere and instill a sense of belonging to the company.Keywords: Organizational, Commitment, Employee, Performance